DIVERSIFIKASI ES KRIM DAUN KELOR (MORINGA OLEIFERA) SEBAGAI PANGAN LOKAL UNTUK MENINGKATKAN IMUNITAS - Wati, Helmina; Wahyudi, Wahyudi; Widyanto, Rinto (Jurnal Abdi Insani, 2024)
KWT Cantik Manis (Canis) is a KWT located in the West Ulin Foundation Village. Wangsa RT/02, which is currently under the auspices of UPT BPP Liang Anggang, is engaged in the cultivation of 10 vegetables, including Moringa leaves, Brazilian spinach, cauliflower, chickpeas, tomatoes, and ornamental plants, within the KWT Canis. These crops are currently being cultivated for consumption and sale to members of the community. Moringa leaves, in particular, are of high nutritional value and are readily available in the surrounding community, especially within KWT Canis. The use of moringa leaves is solely for producing a clear vegetable. The immune systems of children differ significantly from those of adults, necessitating the enhancement of children's immunity to maintain their health. Ice cream is a popular food product, particularly among children. The incorporation of moringa leaves into ice cream can enhance its nutritional profile, particularly in terms of protein and calcium content. The objective of this activity is to enhance the knowledge and abilities of KWT Canis women in the production of moringa leaf ice cream. The methodology employed encompasses the preliminary preparation stage, the implementation phase, which entails counseling and guidance in the preparation of moringa ice cream, and the evaluation of the aforementioned activities. The outcomes of this activity include the acquisition of additional knowledge and skills pertinent to the preparation of moringa ice cream. Conclusion: There has been an enhancement in the abilities and knowledge of KWT Canis mothers in the production of moringa ice cream.